Pendekatan Double Movement Fazlur Rahman dalam Penafsiran Hadis Kontemporer - Jagat Rayana; Tajul Arifin (Cakrawala: Journal of Religious Studies and Global Society, 2025)
The study of hadith in the Islamic scientific tradition often focuses on the authenticity of sanad and matan, but does not pay attention to the historical context and ethical values contained behind the words and actions of the Prophet Muhammad PBUH. Fazlur Rahman's approach through the concept of Double Movement offers an interpretive framework that combines the understanding of the context of the emergence of the hadith with the withdrawal of universal moral principles that can be applied to contemporary reality. This study aims to analyze the relevance and contribution of this approach in developing a more responsive interpretation of hadith to modern social dynamics. This research uses a qualitative-hermeneutic method with literature study techniques, involving an in-depth analysis of Rahman's primary works as well as relevant hadith literature and contemporary studies. The data was analyzed by tracing the relationship between the hadith texts, their historical context, and the rationalization of moral values produced through the double movement of interpretation. The results of the study show that this approach is effective in bridging the gap between normative texts and the ethical needs of today's society. The double movement approach allows for a more substantive reconstruction of the meaning of the hadith, resulting in an understanding that does not stop at the literal level, but moves towards applicable moral principles. These findings confirm that Rahman's hermeneutic methodology has contributed significantly to the development of contemporary hadith studies, particularly in the context of ethical ijtihad and the renewal of Islamic thought.